Measuring Gender Attitudes Using List Experiments - M Niaz Asadullah; Elisabetta De Cao; Fathema Zhura Khatoon; Zahra Siddique (Global Labor Organization (GLO), 2020)
We elicit adolescent girls' attitudes towards intimate partner violence and child marriage using purposefully collected data from rural Bangladesh. Alongside direct survey questions, we conduct list experiments to elicit true preferences for intimate partner violence and marriage before age eighteen. Responses to direct survey questions suggest that very few adolescent girls in the study accept the practises of intimate partner violence and child marriage (5% and 2%). However, our list experiments reveal significantly higher support for both intimate partner violence and child marriage (at 30% and 24%). We further investigate how numerous variables relate to preferences for egalitarian gender norms in rural Bangladesh.
Keywords: I15; O10; C13; C83; 330; list experiment; indirect response survey methods; intimate partner violence; child marriage; Bangladesh